HALAL BI HALAL, A FESTIVAL OF IDUL FITRI AND ITâS RELATION WITH THE HISTORY OF ISLAMIZATION IN JAVA - Hakam, Saiful (IAIN Tulungagung, 2015)
Dalam artikel ini saya akan membahas tiga topik: Idul Fitri, tradisi halal bi halal dan sejarah islamisasi di Jawa. Berdasarkan gagasan Robert Redfied tentang tradisi besar dan kecil, saya ingin mengatakan bahwa festival Idul Fitri di Jawa lebih menyenangkan, ceria dan menggembirakan daripada di negara asal karena di masa lalu para intelektual yang menyebarkan Islam tidak mencoba untuk mengubah secara radikal tradisi lokal, namun mereka memilih untuk melanjutkan-tradisi kuno dengan agama baru dari tradisi besar Islam. Itu adalah gerakan yang sangat halus dan pintar sebab mereka menghidupkan kembali tradisi kuno dengan memadukannya dengan Islam. In this paper I will discuss three topic: the origin of Idul Fitri, the halal bi halal tradition and the history of Islamization in Java. Based on Robert Redfiedâs notion of great tradition and little tradition, I want to argue that the festival of Idul Fitri in Java is more happy, cheery, and merry rather than in the origin country because in the past the intellectuals who propagated Islam did not try to change radically the local traditions, however they preferred to recontinue the ancient traditions with a new religion from great tradition, Islam. It was a very smooth and smart movement because they revive the ancient traditions by Islamizing the ancient tradition.